The Influence of Work-Life Balance and Compensation on Performance Using Job Satisfaction in Nurses at Cilacap Regional Hospital - Azizah, Lisda Fathul; Purnadi, Purnadi; Bagis, Fatmah; Haryanto, Totok (PT FORMOSA CENDEKIA GLOBAL, 2025)
Nurse performance is still a factor that needs to be considered and improved, especially in the health service sector in Cilacap, Indonesia. This study has the aim to determine the effects of work-life balance and compensation on performance, with a mediating variable, which is job satisfaction. The questionnaire was given directly using a quantitative approach with a sampling technique using purposive sampling. The population in this study was 215 and the sample used was 140 respondents from nurses at Cilacap Regional Hospital. This study used SEM-PLS to analyze the data. The findings showed that, even though compensation did not have a direct effect on performance and work-life balance did not have a direct effect on job satisfaction, both had significant effects on job satisfaction, which means there is a positive relationship between work-life balance with compensation on performance through job satisfaction.